Single and hybrid electromagnetic absorbing coatings on polyacrylonitrile precursor to motivate the microwave pre-oxidation. (December 2018) - Elagib, Tienah H.H.; Hassan, Elwathig A.M.; Fan, Cheng; Han, Keqing; Yu, Muhuo
Abstract: Nano silicon carbide was used separately and as an auxiliary absorber for the modification of the PAN precursor fibers to upgrade their microwave absorbability in order to undergo the subsequent pre-oxidization by using microwave. Surface coatings were successfully applied to the PAN precursor and the coated fibers were pre-oxidized over the microwave furnace for 60 min. To study the effect of the coatings on the pre-oxidized fibers, a series of characterizations were carried out. FTIR analysis results showed clear changes in the basic chemical structure of pre-oxidized fibers, which approved the occurrence of the cyclization and crosslinking reactions. Furthermore, the cyclization was confirmed by the thermal analysis results. According to the listed oxygen values, it can be suggested that the pre-oxidized fibers can resist the high temperatures in the following stage (carbonization). In addition, the crystalline analysis revealed a reduction in crystallinity, while the mechanical analysis demonstrated a reduction in tensile strength and elongation at break of pre-oxidized fibers. Highlights: Single and hybrid coating were applied on PAN fibers. Coated fibers were used as precursors for the microwave pre-oxidation process. The pre-oxidation led to polymer decrystallization, cyclization and cross linking reaction. The polymer crosslinking induced the rearrangement of layer plane cause change of the microstructure parameters. More developed conjugated structure was obtained in pre-oxidized hybrid fibers.